Types of Reading in PISA 2018: Reviewed from The Students Base on Gender - Safari, NFN (Indonesian Journal of Educational Assessment, 2021)
The main objective of this study is to answer the following questions. Are there differences in the perception of male and female students on the type of reading (magazine, fiction, non-fiction, comic book, newspaper) on the 2018 PISA test? The research method used is a quantitative method. The data in this study uses PISA 2018 data which has been released to the public and has been permitted to be used for research development purposes. The population of this study is 15 year old students (junior high school) worldwide who are studying in 2018, while the sample is 15 year old students taking PISA tests in 80 countries. The reason for selecting the sample was students who were taking the 2018 PISA test. The data in this study was in the form of a questionnaire that was answered by students in 80 countries, namely 612004 students from 80 countries. Based on the results of the T-test analysis, the results showed that there were differences in the perceptions of male and female students on the perception of the type of reading on the 2018 PISA test, P < 0.000. The types of reading that female students like are: magazines (2.43%), fiction, and non-fiction (3.24%); while the types of reading favored by male students are: comic books (2.28%) and newspapers (2.51%). The reliability of the instrument is 1.00 higher than the reliability of the person = 0.15. The conclusion is that there are differences in the perception of male and female students on the perception of the type of reading on the 2018 PISA test, P < 0.000. The types of reading that female students like or read a lot are: magazine, fiction, and non-fiction; while the types of reading that male students prefer or read are: comic books and newspapers.